MOTIVATION OF PROFESSIONAL ACTIVITIES OF MANAGERS OF SECONDARY EDUCATION INSTITUTIONS IN KYIV - Lynov, Kostiantyn; Merzliakova, Olena; Sabol, Diana; Kotsiuba, Hanna (Educological discourse, 2022)
The article presents the results of a research of the features of the motivational sphere of of the administrators (principals and their assistants) of Institutions of general secondary education, conducted by the Chair of Educational Leadership of Borys Grinchenko Kyiv University in October-November 2021. This was a pilot phase of the study, which covered 208 people holding senior positions in secondary schools in Kyiv. The purpose of the pilot phase was to study the motivational sphere of managers, which involves identifying the most common motives, the ratio of internal and external motivation of respondents, the dynamics of changes in motivational complexes depending on seniority, as well as the interaction of motives with their attitude to innovation in education. Regarding the tasks, the method «Motivation of professional activity» by K. Zamfir in a modification of A. Rean, was chosen. The research showed that the most important motives of professional activity for the leaders of secondary schools are: satisfaction with the process and results of their work; opportunities for self-realization in management; the receiving of adequate monetary remuneration for their work. The key determining factor for the respondents is the internal motivation for the managerial activity. Internal motivation remains dominant throughout the period of activity. Most respondents have a positive attitude towards innovation, combined with a high level of internal motivation. A further perspective of the study may be the creation of an appropriate psycho-correctional program aimed at increasing internal motivation and further improving the reform steps in the field of education. Also, a separate task may be to study the dynamics of the motivational sphere under the influence of the challenges of the war in Ukraine.